Coeliac disease and goitre. - Robinson, T. J. (BMJ Group, 1977)
Two cases of coeliac disease associated with thyroid enlargement are presented. One had a large simple adenomatous goitre which was removed surgically and the other had histological confirmation of lymphadenoma (Hashimoto's disease).